1995
DOI: 10.2331/fishsci.61.327
|View full text |Cite
|
Sign up to set email alerts
|

Post-mortem Change of Three-dimensional Structure of Collagen Fibrillar Network in Fish Muscle Pericellular Connective Tissues Corresponding to Post-mortem Tenderization

Abstract: The three-dimensional structure of a collagen fibrillar network was examined by using a cell-macer ation/SEM method combined with measuring the breaking strength of rainbow trout, yellowtail, and tiger puffer muscles. Rainbow trout and yellowtail muscles were tenderized during storage, but tiger puffer muscle showed no tenderization even after 72 h storage. According to histological observations, the thickness of pericellular connective tissue in rainbow trout and yellowtail muscles became thinner, and the den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 11 publications
2
50
0
2
Order By: Relevance
“…Some studies point out that muscle‐softening occurring in fish throughout post‐mortem storage is the result of the degradation of myofibrillar components . However, other studies consider that the breakdown of collagen fractions of the extracellular matrix is responsible for those textural changes . The relative importance of degradation of each component is still unclear, and depends on the species and other factors before and after slaughtering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies point out that muscle‐softening occurring in fish throughout post‐mortem storage is the result of the degradation of myofibrillar components . However, other studies consider that the breakdown of collagen fractions of the extracellular matrix is responsible for those textural changes . The relative importance of degradation of each component is still unclear, and depends on the species and other factors before and after slaughtering.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that textural changes occurring in fish muscle during post‐mortem storage are the result of the degradation of myofibrillar components . However, other studies consider the breakdown of the extracellular collagen fractions as responsible for these changes, given that collagen is the major component of connective tissue, and it is considered a substantial contributor to textural properties of fish flesh …”
Section: Introductionmentioning
confidence: 99%
“…4 and 5). Collagen fibrils in the pericellular connective tissue were observed, which had a close relationship to post-mortem softening of muscle (Ando et al, 1992(Ando et al, , 1995Sato et al, 1997). In the case of yellowtail (Fig.…”
Section: Histological Observationsmentioning
confidence: 93%
“…On the other hand, several studies (Sato et al. 1994; Ando et al. 1995; Bremner 1999) have also pointed out that the alterations in textural properties of fish muscle are the result of the disintegration of the extracellular matrix, and thus, the different collagen fractions would be involved in these processes, possibly by the action of endogenous muscle collagenases (Bracho and Haard 1996).…”
Section: Discussionmentioning
confidence: 99%